Mineral flotation inhibitor and preparation method and application thereof

By using maleic anhydride-citric acid-acrylic acid copolymer as mineral flotation inhibitors, the problems of poor magnesium oxide removal effect and high flotation cost in the prior art are solved, and efficient metal recovery and magnesium removal are achieved, reducing the number of times of being abolished. Dosage and cost.

CN119463024APending Publication Date: 2025-02-18LANZHOU UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411591904.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing mineral flotation inhibitors have limited effect in reducing the magnesium oxide content in concentrates, and increasing the amount will lead to an increase in flotation cost, which cannot meet the high demand for flotation of sulfide ore.

Method used

Maleic anhydride-citric acid-acrylic acid copolymer is used as a mineral flotation inhibitor, and reacts with magnesium elements on the surface of gangue minerals such as serpentine to change the Zeta potential on the mineral surface, and eliminates heterophasic agglomeration by electrostatic repulsion.

Benefits of technology

The copper-nickel metal grade and recovery rate in concentrates are improved, while the removal effect of magnesium oxide is enhanced, the amount of mineral flotation inhibitors is used, and the flotation cost is significantly reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463024A_ABST
    Figure CN119463024A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of mineral flotation, and provides a mineral flotation inhibitor and a preparation method and application thereof. The preparation method of the mineral flotation inhibitor comprises the following steps: reacting maleic anhydride, citric acid and water to obtain a maleic anhydride-citric acid monomer; a maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water are subjected to a reaction, and the mineral flotation inhibitor maleic anhydride-citric acid-acrylic acid copolymer is obtained. The mineral flotation inhibitor reacts with magnesium elements on the surfaces of gangue minerals such as serpentine through chemical adsorption, the Zeta potential on the surfaces of the gangue minerals such as serpentine is changed, and out-phase condensation between metal sulfide ore and the gangue minerals is effectively eliminated through electrostatic repulsion in the alkalescent flotation environment; the grade and the recovery rate of copper and nickel metal in the concentrate are improved, and meanwhile the removal effect of the magnesium element is improved; the raw materials are wide in source and low in price, and the preparation method is simple, efficient and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of mineral flotation, and in particular to a mineral flotation inhibitor and a preparation method and application thereof. Background Art

[0002] Magnesium-rich silicate minerals are the main gangue minerals of metal sulfide ores in my country, including serpentine, talc, chlorite, etc. Magnesium-rich silicate minerals have low hardness and are too fine during grinding, resulting in fine-grained gangue minerals covering the surface of the minerals during flotation. On the one hand, this will reduce the recovery rate of metal sulfide ores, and on the other hand, it will enter the concentrate along with the sulfide ore, resulting in an excessively high magnesium oxide content in the concentrate, increasing the difficulty of subsequent smelting.

[0003] In the research on reducing the content of magnesium oxide in concentrate, small molecular compounds such as sodium hexametaphosphate, water glass, citric acid, and macromolecular compounds such as sodium carboxymethyl cellulose (CMC) and polyaspartic acid have been widely used. However, with the continuous mining of minerals, the impoverishment of minerals has become more and more obvious. The existing flotation inhibitors have limited effect on the removal of magnesium oxide and it is difficult to meet the high demand for sulfide ore flotation. Although the existing flotation inhibitors can improve the flotation effect of sulfide ores by increasing the dosage, this will greatly increase the flotation cost.

[0004] Therefore, there is an urgent need to develop new flotation depressants that can improve the metal grade in the concentrate at a low cost and increase the removal efficiency of magnesium oxide to meet the current needs of sulfide ore flotation. Summary of the invention

[0005] The purpose of the present invention is to provide a mineral flotation depressant and a preparation method and application thereof in view of the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a mineral flotation depressant, comprising the following steps:

[0008] (1) reacting maleic anhydride, citric acid and water to obtain a maleic anhydride-citric acid monomer;

[0009] (2) reacting maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water to obtain a mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

[0010] Preferably, the mass volume ratio of maleic anhydride, citric acid and water in step (1) is 2.5 g: 4-6 g: 30-50 mL.

[0011] Preferably, the reaction temperature in step (1) is 80-100° C., the reaction time is 8-12 h, and the reaction pH is 2-4.

[0012] Preferably, in step (2), the mass volume ratio of the maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water is 0.5-1 g: 0.5-3 g: 0.05-0.3 g: 30-50 mL.

[0013] Preferably, the reaction temperature in step (2) is 80-100° C., and the reaction time is 3-8 h.

[0014] Preferably, the molecular weight of the mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer is 10,000 to 20,000 Da.

[0015] The invention also provides a mineral flotation inhibitor prepared by the preparation method.

[0016] The present invention also provides the use of the mineral flotation inhibitor in the flotation of magnesium-rich silicate minerals. The mineral flotation inhibitor is added to the magnesium-rich silicate mineral for flotation, and the mass ratio of the magnesium-rich silicate mineral to the mineral flotation inhibitor is 1t:50-100g.

[0017] Beneficial effects of the present invention:

[0018] The mineral flotation depressant of the present invention reacts with magnesium on the surface of gangue minerals such as serpentine through chemical adsorption, changes the Zeta potential on the surface of gangue minerals such as serpentine, effectively eliminates heterogeneous agglomeration between metal sulfide ores and gangue minerals through electrostatic repulsion in a weakly alkaline flotation environment, improves the copper and nickel metal grade and recovery rate in the concentrate, and improves the removal effect of magnesium at the same time; the raw material source of the present invention is wide and cheap, the preparation method is simple and efficient, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The C1s X-ray photoelectron spectrum of the serpentine surface without adding mineral flotation depressants;

[0020] Figure 2 The C1s X-ray photoelectron spectrum of the serpentine surface to which the mineral flotation depressant of Example 1 is added;

[0021] Figure 3 Mg 1s X-ray photoelectron spectra of the serpentine surface without adding the mineral flotation inhibitor and adding the mineral flotation inhibitor of Example 1;

[0022] Figure 4The Si 2p X-ray photoelectron spectra of the serpentine surface without adding the mineral flotation inhibitor and adding the mineral flotation inhibitor of Example 1;

[0023] Figure 5 is the Zeta potential of each mineral at different pH values;

[0024] Figure 6 The present invention is a flotation flow chart for flotation using the mineral flotation depressant of the present invention. DETAILED DESCRIPTION

[0025] The present invention provides a method for preparing a mineral flotation depressant, comprising the following steps:

[0026] (1) reacting maleic anhydride, citric acid and water to obtain a maleic anhydride-citric acid monomer;

[0027] (2) reacting maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water to obtain a mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

[0028] In the present invention, the mass volume ratio of maleic anhydride, citric acid and water in step (1) is preferably 2.5g:4-6g:30-50mL, more preferably 2.5g:4.8-5.5g:35-45mL, and more preferably 2.5g:5.2g:40mL.

[0029] In the present invention, the reaction temperature in step (1) is preferably 80-100°C, more preferably 85-95°C, more preferably 90°C; the reaction time is preferably 8-12h, more preferably 9-11h, more preferably 10h; the reaction pH is preferably 2-4, more preferably 2.5-3.5, more preferably 3.

[0030] In the present invention, hydrochloric acid is preferably used to adjust the pH value of the reaction in step (1), and the mass concentration of the hydrochloric acid is preferably 30-40%, and more preferably 35-37%.

[0031] In the present invention, the mass volume ratio of the maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water in step (2) is preferably 0.5-1g: 0.5-3g: 0.05-0.3g: 30-50mL, more preferably 0.6-0.9g: 1-2g: 0.075-0.2g: 35-45mL, and more preferably 0.75g: 1.5g: 0.15g: 40mL.

[0032] In the present invention, in step (2), preferably, maleic anhydride-citric acid monomer is first mixed with the first part of water to obtain a maleic anhydride-citric acid monomer solution, acrylic acid is mixed with the second part of water to obtain an acrylic acid solution, and ammonium persulfate is mixed with the third part of water to obtain an ammonium persulfate solution; the volume ratio of the first part of water, the second part of water and the third part of water is preferably 1-2:1-2:1-2, and more preferably 1.5:1.5:1.5.

[0033] In the present invention, it is preferred that the maleic anhydride-citric acid monomer solution is first mixed with the first part of the ammonium persulfate solution to obtain a first mixed solution, the acrylic acid solution and the second part of the ammonium persulfate solution are dropwise added to the first mixed solution to obtain a second mixed solution, and the third part of the ammonium persulfate solution is dropwise added to the second mixed solution to obtain a reaction solution, and the reaction is started after the dropwise addition is completed.

[0034] In the present invention, the dropping speed is independently preferably 1 to 3 drops / s, more preferably 2 drops / s.

[0035] In the present invention, it is preferred to heat the first mixed solution first, and then dropwise add the acrylic acid solution and the second part of the ammonium persulfate solution, and the heating temperature is preferably 70 to 90° C., and more preferably 80° C.; it is preferred to stir the second mixed solution first, and then dropwise add the third part of the ammonium persulfate solution, and the stirring speed is preferably 600 to 1200 r / min, and more preferably 800 to 1000 r / min, and the stirring time is preferably 1 to 3 h, and more preferably 2 h.

[0036] In the present invention, the volume ratio of the first part of the ammonium persulfate solution, the second part of the ammonium persulfate solution and the third part of the ammonium persulfate solution is preferably 0.5-1.5:2-4:0.5-1.5, and more preferably 1:3:1.

[0037] In the present invention, the reaction temperature in step (2) is preferably 80-100°C, more preferably 85-95°C, and more preferably 90°C; the reaction time is preferably 3-8h, more preferably 4-7h, and more preferably 5-6h.

[0038] In the present invention, stirring is preferably performed during the reaction in step (2), and the stirring speed is preferably 600 to 1200 r / min, and more preferably 800 to 1000 r / min.

[0039] In the present invention, after the reaction in step (2) is completed, it is preferred to adjust the pH value of the reaction system first, then add anhydrous ethanol to precipitate and filter, so as to obtain the mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

[0040] In the present invention, after the reaction in step (2) is completed, the pH value of the reaction system is preferably adjusted to 6.5-7.5, more preferably to 7, the reagent used to adjust the pH value of the reaction system is preferably sodium hydroxide solution, and the mass concentration of the sodium hydroxide solution is preferably 35-45%, more preferably 40%; the volume ratio of anhydrous ethanol to the reaction solution is preferably 3-6:1, more preferably 4-5:1.

[0041] In the present invention, the molecular weight of the mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer is preferably 10000-20000 Da, more preferably 12000-18000 Da, and more preferably 15000 Da.

[0042] In the present invention, the synthesis route of the mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer (MACA-AA) is as follows:

[0043]

[0044] The invention also provides a mineral flotation inhibitor prepared by the preparation method.

[0045] The present invention also provides the use of the mineral flotation depressant in the flotation of magnesium-rich silicate minerals. The mineral flotation depressant is added to the magnesium-rich silicate mineral for flotation. The mass ratio of the magnesium-rich silicate mineral to the mineral flotation depressant is preferably 1t:50-100g, further preferably 1t:60-90g, and more preferably 1t:75g.

[0046] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0047] Example 1

[0048] 2.5 g of maleic anhydride (MA), 4.8 g of citric acid (CA) and 30 mL of distilled water were mixed, and the pH value of the mixture was adjusted to 3 with 37% hydrochloric acid. The mixture was heated to 90°C for 8 h. After the reaction was completed, it was naturally cooled until a white solid precipitated, and filtered to obtain maleic anhydride-citric acid monomer (MACA).

[0049] Dissolve 0.5g of maleic anhydride-citric acid monomer, 0.5g of acrylic acid (AA), and 0.075g of ammonium persulfate in 10mL of water respectively to obtain maleic anhydride-citric acid monomer solution, acrylic acid solution, and ammonium persulfate solution. First, mix the maleic anhydride-citric acid monomer solution and the first part of the ammonium persulfate solution (the first part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to obtain a first mixed solution, and heat the first mixed solution to 80°C. Add the acrylic acid solution and the second part of the ammonium persulfate solution (the second part of the ammonium persulfate solution is 60% of the total volume of the ammonium persulfate solution) to the first mixed solution at a rate of 2 drops / s to obtain a second mixed solution, and stir the second mixed solution at a speed of 800r / min for 2h. Add the third part of the ammonium persulfate solution (the third part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to the second mixed solution at a rate of 2 drops / s to obtain a reaction solution. Heat the reaction solution to 95°C and stir the reaction at a speed of 800r / min for 3h. After the reaction is completed, a sodium hydroxide solution with a mass concentration of 40% is used to adjust the pH value of the reaction system to 7, and then anhydrous ethanol is added (the volume ratio of anhydrous ethanol to the reaction solution is 4:1) to precipitate the reaction system, and the precipitate is filtered to obtain a mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

[0050] The mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer prepared in this example is marked as MACA-AA-1, and has a molecular weight of 18500 Da.

[0051] Figure 1 This is the C1s X-ray photoelectron spectrum of the serpentine surface without adding mineral flotation depressants. Figure 1 It can be seen that a carbon peak appears on the surface of serpentine, and three peaks are fitted in the C1s spectrum at 284.80 eV, 286.64 eV, and 289.33 eV, corresponding to CC, CO, and carbonate binding energies, respectively. Figure 2 This is the C1s X-ray photoelectron spectrum of the serpentine surface to which the mineral flotation depressant of Example 1 is added. Figure 1 , Figure 2 It can be seen that the C1s spectra at the binding energies of CC, CO, and carbonate changed due to the adsorption of mineral flotation depressants on the serpentine surface.

[0052] Figure 3 Mg 1s X-ray photoelectron spectra of the serpentine surface without adding mineral flotation inhibitor and adding the mineral flotation inhibitor of Example 1. Figure 3 It can be seen that after the action of mineral flotation depressant, the Mg1s binding energy on the serpentine surface changes by 0.66 eV, indicating that the maleic anhydride-citric acid-acrylic acid copolymer acts on the serpentine surface by chemical adsorption.

[0053] Figure 4 The Si 2p X-ray photoelectron spectra of the serpentine surface without adding the mineral flotation inhibitor and adding the mineral flotation inhibitor of Example 1 are shown in FIG. Figure 4 It can be seen that maleic anhydride-citric acid-acrylic acid copolymer has almost no interaction with the silicon element on the serpentine surface.

[0054] Figure 5 is the Zeta potential of each mineral at different pH values. Figure 5 It can be seen that when pH < 11, the surface charge of serpentine is positive and the surface charge of pyrite is negative. When the flotation test is performed, the pH value is about 8, so heterogeneous coagulation occurs between the negatively charged pyrite and the positively charged serpentine. After adding the mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer of Example 1, the surface charges of pyrite and serpentine are -36.15mV and -28.33mV, respectively, indicating that the charge polarity of the two minerals is the same, the two minerals repel each other due to electrostatic interaction, and heterogeneous coagulation is effectively eliminated.

[0055] Example 2

[0056] The mass of acrylic acid in Example 1 was modified to 1 g, and the rest was the same as in Example 1.

[0057] The mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer prepared in this example is marked as MACA-AA-2, and has a molecular weight of 20,000 Da.

[0058] Example 3

[0059] The mass of acrylic acid in Example 1 was modified to 1.5 g, and the rest was the same as in Example 1.

[0060] The mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer prepared in this example is labeled as MACA-AA-3 and has a molecular weight of 18000 Da.

[0061] Example 4

[0062] 2.5 g of maleic anhydride (MA), 6 g of citric acid (CA) and 50 mL of distilled water were mixed, and the pH value of the mixture was adjusted to 2 with 30% hydrochloric acid. The mixture was heated to 80°C for 12 h. After the reaction was completed, it was naturally cooled until a white solid precipitated, and filtered to obtain maleic anhydride-citric acid monomer (MACA).

[0063] Dissolve 1g of maleic anhydride-citric acid monomer, 3g of acrylic acid (AA), and 0.3g of ammonium persulfate in 15mL of water respectively to obtain maleic anhydride-citric acid monomer solution, acrylic acid solution, and ammonium persulfate solution. First, mix the maleic anhydride-citric acid monomer solution and the first part of the ammonium persulfate solution (the first part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to obtain a first mixed solution, and heat the first mixed solution to 70°C. Add the acrylic acid solution and the second part of the ammonium persulfate solution (the second part of the ammonium persulfate solution is 60% of the total volume of the ammonium persulfate solution) to the first mixed solution at a rate of 2 drops / s to obtain a second mixed solution, and stir the second mixed solution at a speed of 800r / min for 3h. Add the third part of the ammonium persulfate solution (the third part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to the second mixed solution at a rate of 2 drops / s to obtain a reaction solution. Heat the reaction solution to 80°C and stir the reaction at a speed of 800r / min for 8h. After the reaction is completed, a sodium hydroxide solution with a mass concentration of 40% is used to adjust the pH value of the reaction system to 7, and then anhydrous ethanol is added (the volume ratio of anhydrous ethanol to the reaction solution is 5:1) to precipitate the reaction system, and the precipitate is filtered to obtain a mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

[0064] The mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer prepared in this example is marked as MACA-AA-4, and has a molecular weight of 12000 Da.

[0065] Example 5

[0066] 2.5 g of maleic anhydride (MA), 5.2 g of citric acid (CA) and 40 mL of distilled water were mixed, and the pH value of the mixture was adjusted to 3 with 40% hydrochloric acid. The mixture was heated to 100°C for 10 hours of reaction. After the reaction was completed, it was naturally cooled until a white solid precipitated, and filtered to obtain maleic anhydride-citric acid monomer (MACA).

[0067] Dissolve 0.75g of maleic anhydride-citric acid monomer, 2g of acrylic acid (AA), and 0.2g of ammonium persulfate in 15mL of water respectively to obtain maleic anhydride-citric acid monomer solution, acrylic acid solution, and ammonium persulfate solution. First, mix the maleic anhydride-citric acid monomer solution and the first part of the ammonium persulfate solution (the first part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to obtain a first mixed solution, and heat the first mixed solution to 90°C. Add the acrylic acid solution and the second part of the ammonium persulfate solution (the second part of the ammonium persulfate solution is 60% of the total volume of the ammonium persulfate solution) to the first mixed solution at a rate of 3 drops / s to obtain a second mixed solution, and stir the second mixed solution at a speed of 1200r / min for 2h. Add the third part of the ammonium persulfate solution (the third part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to the second mixed solution at a rate of 2 drops / s to obtain a reaction solution. Heat the reaction solution to 100°C and stir the reaction at a speed of 800r / min for 5h. After the reaction is completed, a sodium hydroxide aqueous solution with a mass concentration of 40% is used to adjust the pH value of the reaction system to 7, and then anhydrous ethanol is added (the volume ratio of anhydrous ethanol to the reaction solution is 3:1) to precipitate the reaction system, and the precipitate is filtered to obtain a mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

[0068] The mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer prepared in this example is labeled as MACA-AA-5 and has a molecular weight of 17000 Da.

[0069] Comparative Example 1

[0070] Dissolve 0.5g of maleic anhydride, 1g of acrylic acid (AA), and 0.075g of ammonium persulfate in 10mL of water respectively to obtain maleic anhydride solution, acrylic acid solution, and ammonium persulfate solution. First, mix the maleic anhydride solution and the first part of the ammonium persulfate solution (the first part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to obtain a first mixed solution, and heat the first mixed solution to 80°C. Add the acrylic acid solution and the second part of the ammonium persulfate solution (the second part of the ammonium persulfate solution is 60% of the total volume of the ammonium persulfate solution) to the first mixed solution at a rate of 2 drops / s to obtain a second mixed solution, and stir the second mixed solution at a speed of 800r / min for 2h. Add the third part of the ammonium persulfate solution (the third part of the ammonium persulfate solution is 20% of the total volume of the ammonium persulfate solution) to the second mixed solution at a rate of 2 drops / s to obtain a reaction solution. Heat the reaction solution to 95°C and stir the reaction at a speed of 800r / min for 3h. After the reaction is completed, a sodium hydroxide solution with a mass concentration of 40% is used to adjust the pH value of the reaction system to 7, and then anhydrous ethanol is added (the volume ratio of anhydrous ethanol to the reaction solution is 4:1) to precipitate the reaction system, and the precipitate is filtered to obtain the mineral flotation depressant maleic anhydride-acrylic acid copolymer.

[0071] The mineral flotation depressant maleic anhydride-acrylic acid copolymer prepared in this example is marked as MA-AA and has a molecular weight of 10000 Da.

[0072] A low-grade copper-nickel sulfide ore in Gansu was selected, with a nickel grade of 0.51%, a copper grade of 0.33%, a magnesium oxide content of 27.86%, and gangue minerals mainly including serpentine, chlorite and talc. The grinding fineness distribution was: the mass proportion of ≤200 mesh was 75%.

[0073] Application Example 1

[0074] Add the mineral flotation depressant MACA-AA-1 of Example 1, copper sulfate, butyl xanthate, and 2# oil to the above copper-nickel sulfide ore, and the mass ratio of the mineral flotation depressant MACA-AA-1, copper sulfate, butyl xanthate, 2# oil, and copper-nickel sulfide ore is 50g:100g:120g:100g:1t. After a flotation process of one roughing, two sweeping, and three finishing, a copper-nickel mixed concentrate is obtained.

[0075] The nickel grade of the copper-nickel mixed concentrate obtained in this application example is 7.62%, the copper grade is 7.89%, and the magnesium oxide content is 6.4%. Compared with the concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.9%, the copper recovery rate is increased by 1%, the nickel grade is increased by 0.6%, the nickel recovery rate is increased by 0.8%, and the magnesium oxide content is reduced by 0.9%.

[0076] Application Example 2

[0077] Add the mineral flotation depressant MACA-AA-2 of Example 2, copper sulfate, butyl xanthate, and 2# oil to the above copper-nickel sulfide ore, and the mass ratio of the mineral flotation depressant MACA-AA-2, copper sulfate, butyl xanthate, 2# oil, and copper-nickel sulfide ore is 50g:100g:120g:100g:1t. After a two-stage flotation process of one roughing, two sweeping, and three finishing, a copper-nickel mixed concentrate is obtained.

[0078] In the first-stage copper-nickel mixed concentrate 1 obtained in this application example, the nickel grade is 7.60%, the copper grade is 7.86%, and the magnesium oxide content is 6.0%. Compared with the first-stage concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.8%, the copper recovery rate is increased by 1%, the nickel grade is increased by 0.55%, the nickel recovery rate is increased by 0.5%, and the magnesium oxide content is reduced by 0.5%.

[0079] In the second-stage copper-nickel mixed concentrate 2 obtained in this application example, the nickel grade is 2.75%, the copper grade is 4.74%, and the magnesium oxide content is 12.62%. Compared with the second-stage concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.7%, the copper recovery rate is increased by 1.5%, the nickel grade is increased by 0.5%, the nickel recovery rate is increased by 0.6%, and the magnesium oxide content is reduced by 3%.

[0080] Application Example 3

[0081] Add the mineral flotation depressant MACA-AA-2 of Example 2, copper sulfate, butyl xanthate, and 2# oil to the above copper-nickel sulfide ore, and the mass ratio of the mineral flotation depressant MACA-AA-2, copper sulfate, butyl xanthate, 2# oil, and copper-nickel sulfide ore is 75g:100g:120g:100g:1t. After a two-stage flotation process of one roughing, two sweeping, and three finishing, a copper-nickel mixed concentrate is obtained.

[0082] In the first-stage copper-nickel mixed concentrate 1 obtained in this application example, the nickel grade is 7.45%, the copper grade is 7.61%, and the magnesium oxide content is 6.3%. Compared with the first-stage concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.62%, the copper recovery rate is increased by 1.2%, the nickel grade is increased by 0.45%, the nickel recovery rate is increased by 0.5%, and the magnesium oxide content is reduced by 0.3%.

[0083] In the second-stage copper-nickel mixed concentrate 2 obtained in this application example, the nickel grade is 2.80%, the copper grade is 4.82%, and the magnesium oxide content is 12.60%. Compared with the second-stage concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.8%, the copper recovery rate is increased by 1.6%, the nickel grade is increased by 0.7%, the nickel recovery rate is increased by 0.8%, and the magnesium oxide content is reduced by 3.3%.

[0084] Comparative application example 1

[0085] Add the mineral flotation depressant MA-AA of Comparative Example 1, copper sulfate, butyl xanthate, and 2# oil to the above copper-nickel sulfide ore, and the mass ratio of the mineral flotation depressant MA-AA-1, copper sulfate, butyl xanthate, 2# oil, and copper-nickel sulfide ore is 50g:100g:120g:100g:1t. After a flotation process of one roughing, two sweeping, and three refining, a copper-nickel mixed concentrate is obtained.

[0086] The nickel grade of the copper-nickel mixed concentrate obtained in this comparative application example is 7.28%, the copper grade is 7.03%, and the magnesium oxide content is 6.68%. Compared with the concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.3%, the copper recovery rate is increased by 0.5%, the nickel grade is increased by 0.2%, the nickel recovery rate is increased by 0.2%, and the magnesium oxide content is reduced by 0.25%.

[0087] Comparative Application Example 2

[0088] Add mineral flotation inhibitor sodium hexametaphosphate and copper sulfate, butyl xanthate, and 2# oil to the above copper-nickel sulfide ore, and the mass ratio of mineral flotation inhibitor sodium hexametaphosphate, copper sulfate, butyl xanthate, 2# oil, and copper-nickel sulfide ore is 800g:100g:120g:100g:1t. After a flotation process of one roughing, two sweeping, and three refining, a copper-nickel mixed concentrate is obtained.

[0089] The nickel grade of the copper-nickel mixed concentrate obtained in this comparative application example is 7.45%, the copper grade is 7.78%, and the magnesium oxide content is 6.71%. Compared with the concentrate obtained without adding mineral flotation depressants, the copper grade is increased by 0.78%, the copper recovery rate is increased by 1%, the nickel grade is increased by 0.45%, the nickel recovery rate is increased by 0.5%, and the magnesium oxide content is reduced by 0.15%.

[0090] From the analysis of Application Example 1 and Comparative Application Example 2, it can be seen that when the copper and nickel grades and recovery rates of the obtained concentrates are similar, 800 g / t of sodium hexametaphosphate needs to be added as a mineral flotation inhibitor, while only 50 g / t of MACA-AA, the mineral flotation inhibitor of the present invention, needs to be added, which significantly reduces the amount of mineral flotation inhibitor used.

[0091] Analysis of Application Example 1 and Comparative Application Example 1 shows that the copper-nickel grade and recovery rate and magnesium oxide removal efficiency of the concentrate obtained by using the mineral flotation depressant MACA-AA of the present invention are better than those of the mineral flotation depressant MA-AA of the comparative example.

[0092] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a mineral flotation depressant, characterized in that: The following steps are included: (1) reacting maleic anhydride, citric acid and water to obtain a maleic anhydride-citric acid monomer; (2) reacting maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water to obtain a mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer.

2. The preparation method according to claim 1, characterized in that: The mass volume ratio of maleic anhydride, citric acid and water in step (1) is 2.5g:4-6g:30-50mL.

3. The preparation method according to claim 2, characterized in that: The reaction temperature of step (1) is 80-100° C., the reaction time is 8-12 hours, and the reaction pH is 2-4.

4. The preparation method according to claim 1 or 2, characterized in that: The mass volume ratio of the maleic anhydride-citric acid monomer, acrylic acid, ammonium persulfate and water in step (2) is 0.5-1g:0.5-3g: 0.05~0.3g:30~50mL.

5. The preparation method according to claim 4, characterized in that: The reaction temperature in step (2) is 80-100° C., and the reaction time is 3-8 hours.

6. The preparation method according to claim 5, characterized in that: The molecular weight of the mineral flotation depressant maleic anhydride-citric acid-acrylic acid copolymer is 10000-20000 Da.

7. The mineral flotation depressant prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the mineral flotation depressant according to claim 7 in the flotation of magnesium-rich silicate minerals, characterized in that: A mineral flotation depressant is added to a magnesium-rich silicate mineral for flotation, wherein the mass ratio of the magnesium-rich silicate mineral to the mineral flotation depressant is 1 t: 50-100 g.